FI-Lab predicts all-cause mortality, but not successful rehabilitation, among patients aged 65 and older after hip or pelvic fracture - Evgeniya Zikrin; Evgeniya Zikrin; Abdu El Karim Hilali; Abdu El Karim Hilali; David Shacham; David Shacham; Reut Frenkel; Reut Frenkel; Olga Abel; Olga Abel; Muhammad Abo Abed; Muhammad Abo Abed; et al. (Frontiers in Medicine)
PurposeOver the past decade, the Frailty Index based on Laboratory data (FI-Lab index) has been effective in predicting complications during hospitalization, length of hospital stay, changes in functional status, and even mortality. The aims of the present study were to examine the associations between FI-Lab, rehabilitation outcomes, and mortality following hip and pelvic fractures.MethodsA retrospective study of patients 65 years of age and above who underwent rehabilitation after hip or pelvic fracture in the Geriatric Department, between January 2018 and December 2024. Data included demographic variables, comorbidity, and all-cause mortality. The FI-Lab was calculated based on 26 available blood tests, as well as blood pressure and heart rate measurements. Rehabilitation outcomes were measured using the Montebello Rehabilitation Factor Score-Revised (MRFS-R).ResultsData were collected for 753 patients. The mean age was 81.9 ± 7.7 years, and 70.3% were women. The mean FI-Lab score was 0.34 ± 0.11. Based on the distribution of FI-Lab scores by quartiles, patients were categorized into four frailty groups: robust (FI-Lab < 0.251), mild (0.252–0.333), moderate (0.334–0.407), and severe (>0.409). No association was found between FI-Lab and MRFS-R as a continuous variable (Spearman r = −0.07, p = 0.054). A very weak correlation was found between FI-Lab and the length of stay in the Geriatric Department (Spearman r = 0.08, p = 0.022). After adjusting for age, sex, comorbidity, and complications during hospitalization, patients with higher FI-Lab scores exhibited higher mortality rates. For each 0.01 increase in the FI-Lab score (as a continuous variable), adjusted analyses revealed a 3.6% increase in all-cause mortality within the first year after hospitalization, and a 2.7% increase in all-cause mortality during median follow-up period of 2.2 years.ConclusionFI-Lab does not predict rehabilitation success, but does predict overall mortality among patients who underwent rehabilitation after a hip or pelvic fracture.